Pengaruh Arus Kas Investasi, Arus Kas Pendanaan, Arus Kas Operasi dan Laba Bersih terhadap Dividen Kas pada Perusahaan Properti - Dewi Br. Banjarnahor; Norma Sari Nainggolan; Siska Pardede; Anita Pardede (IPM2KPE, 2022)
This study aims to determine the effect of investment cash flow, funding cash flow, operating cash flow, and net income on cash dividends in property companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. This research method is descriptive quantitative. The total population is 60 companies and by using purposive sampling technique, there are 12 companies, and the year of research observation (5) is five years and is obtained from the IDX. Data analysis in the form of multiple linear regression. The results showed that the results of the T test, namely, a) the investment cash flow variable to cash dividends had a t value, namely t-count < t-table, namely -2.659 <1.684 and a significant value of 0.012 <0.05; b) the variable of funding cash flows to cash dividends has a t value of t-count < t-table which is 1.459 <1.684 and a significant value of 1.154 > 0.05; c) operating cash flow variable to cash dividend has a value of t, namely t-count < t-table, namely 0.691 < 1.684 and the significant value is 0.494 > 0.05; d) the variable net income to cash dividends has a value of t, namely t-count < t-table, namely -4.250 <1.684 and the significant value is 0.000 <0.05. The results of the F test showed that the f-count value >f-table was 7.148>2.449 and the significant value was 0.00<0.05. In conclusion, the variables of investment cash flow and net income have a partial and significant effect on cash dividends. Meanwhile, funding cash flow and operating cash flow have no partial and significant effect on cash dividends. Simultaneously, investment cash flow, funding cash flow, operating cash flow, net income have a significant effect on cash dividends. Keywords: Investment Cash Flow, Operating Cash Flow, Funding Cash Flow, Cash Dividend, Profit and Loss